Técnica de Bad Ragaz en niños con Síndrome de Down hipotónicos que asisten a la Unidad Educativa Especializada Carlos Garbay periodo marzo-agosto 2016 - Ortega Huilcapi, Lizeth Ktherine (2016)
The application of the Technique Bad Ragaz in children with syndrome or hypotonic Down attending regularly to the Specialized Education Unit Carlos Garbay was conducted in the period from March to August 2016. The research started with the implementation of a scorecard, by means of which it was determined a group with hypotonic characteristics to work with. This group corresponds to 50 % of people with Down syndrome in this institution, presenting the different particular physical conditions of each patient. To be able to understand an improve the application of the technique, the definition of Down syndrome was presented, which refers to altering the number of chromosomes, resulting in a change in the development of body and brain. Getting involved in the history, epidemiology, causes, types of Down syndrome, general characteristics and health problems presented in this population; a proposal for the execution of exercise in Bad Ragaz technique was perfomed. Muscle tone was defined by G. Holmes in 1992 as light anda constant voltage having healthy muscle, which offers resistance when it moves passively. Taking into account this concept it can be said that hypotonic refers to the loss of strength and tensible capacity experienced by patients with Down syndrome. Hydrotherapy is the use of water as a therapeutic agent in any form or state, and is considered as an essential element in the survival of human beings as mentioned by Sebastian Kneeip through the study of history, clamming that among the benefits of the application of hydrotherapy in patients with Down syndrome is to improve the adaptation to the environment and optimizing postural control and helps to an appropriate respiratory behavior. Thus the research work guided efficiently and correctly, providing comprehensive care to the patient bases on scientific knowledge. Knowing the importance of hydrotherapy, we could be involved in the application of the technique of Bad Ragaz, considering the evolution, development and implementation of it. The technique of Bad Ragaz focuses on the use of the know rings Bad Ragaz, this name comes from the sources found in Switzerland in 1840 and developed in 1960 as a therapeutic technique using water properties that allow directly to improve muscle tone at a temperature of 34 C. – 35 C. The sequence of isotonic, isokinetic isometric and passive exercise allowed us to work with patients in supine and prone with lateral movements. This, has improved significantly the muscle tone helping to the patient’s physical conditions who are able to get adapted better to their environment. This research applied an analysis of the “Bad Rgaz technique in children with Down syndrome hypotonic, who attend Special Education Unit at Carlos Garbay, March- August 2016 period”, with the intention to improve their quality of life. At the end of the research, it was demonstrated that the improvement of muscle tone, directly benefits the normal motor development, helping a functional muscle balance regarding activities of children with Down syndrome.